ANALISIS IMPLEMENTASI AKAD BAGI HASIL LAHAN PERTANIAN DALAM PERSPEKTIFEKONOMI ISLAM - Yuni itna suryani (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to analyze the implementation of agricultural land profit-sharing contracts (Mukhabarah) from an Islamic economic perspective, particularly among rice farmers in Tanjung Aur Seberang Village, Serai Serumpun Subdistrict, Tebo Regency. This research is motivated by the traditional land rental practices that have been passed down through generations in the village, although not all of them are well understood in terms of compliance with Islamic principles. The research uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation involving 13 informants consisting of landowners, tenant farmers, religious figures, and village officials. The results indicate that the Mukhabarah contract is carried out directly between the landowner and the cultivator, both verbally and in writing. Payment is made after harvest, and in the event of crop failure, it can be postponed. This practice is considered in accordance with Islamic economic principles because it fulfills the pillars and requirements of the contract, such as clear object, mutual consent, and lawful purpose. Supporting factors include fertile land and farming skills, while the main obstacle lies in the risk of crop failure. Thus, the implementation of Mukhabarah in this village is not only valid in terms of sharia, but also contributes to the economic sustainability of farmers.